The Role of IFN-alpha in Experimental and Clinical Uveitis. (2nd January 2019) - Liu, Xiaoli; Diedrichs-Möhring, Maria; Wildner, Gerhild
ABSTRACT: Purpose : IFN-α is the only treatment capable of inducing long-term remission in some patients with ocular Behçet's disease. In this review, we focus on immune mechanisms of IFN-α in animal models and patients and compare the outcome of different clinical studies. Methods : Review of literature using PubMed and Google and original data from rat models with monophasic/chronic or relapsing experimental autoimmune uveitis treated with IFN-α. Results : The role of IFN-α and its effect on various cell types were investigated, in some cases with contradictory results. Some patients respond very well to IFN-α treatment, while others are non-responders, which was reflected in the uveitis rat models: relapsing uveitis was ameliorated, the monophasic/chronic disease even aggravated. Conclusions : Despite intensive investigations in patients and animal models, the immune mechanisms explaining the therapeutic effect of IFN-α in ocular Behçet's disease are not yet fully understood and need further investigation.